Kedudukan al-Tas‘īr al-Jabarī dalam Tinjauan Kaidah Yutaḥammal al-Ḍarar al-Khāṣ li Daf‘ al-Ḍarar al-‘Ām - Asnawati Patuti; Afia Hafizah; Aisyah Aisyah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This research aims to find out and understand the law and position of al-tas‘īr al-jabarī in reviewing the rules of yutaḥammal al-ḍarar al-khāṣ li daf‘i al-ḍarar al-‘ām. The type of research used is descriptive qualitative in the form of library research with a normative and sociological approach. The research results show that al-tas'īr al-jabarī is a government policy in the form of intervention to set certain prices for goods, food and services, which the public is obliged to comply with. Al-tas‘īr al-jabarī has different positions depending on market conditions. Under normal conditions, the al-tas‘īr al-jabarī policy is not needed so its position returns to its original law, namely that it cannot be carried out. However, in abnormal conditions, the al-tas'īr al-jabarī policy can be a solution so that it can be done to prevent al-ḍarar al-'ām which will befall a large number of people, even though it has to bear the al-ḍarar al-khāṣ which will befall certain individuals or groups as a result of al-tas'īr al-jabarī's policies.